Penggunaan Sistem Pembayaran Nirkontak untuk Mencegah Penyebaran Covid-19 di Indonesia - Kotjoprayudi, Raswyshnoe Boing; Kastaman, Kastaman (@is The Best : Accounting Information Systems and Information Technology Business Enterprise, 2023)
World Health Organization has classified COVID-19 as a pandemic. Many hotels were forced to close because no guests came. Scientists agree that COVID-19 cannot be stopped, experts believe it can be delayed greatly using current "social distancing". This study aims to support the development of payment applications using the Contactless Payment (CP) method by presenting statistical data usage in people around the world. CP payments have become popular and are more accepted as a new payment method in both developed and developing countries. CP continues to grow and influences many factors such as greater spread, financial inclusion, and becoming more convenient, faster, and cheaper. CPs like this play an important role in shaping ecosystems, from regulators, financial institutions, toolmakers, retailers, or vendors, to consumers themselves. The results demonstrated that the technology developed was capable of speeding up and simplifying the hotel booking transaction process. The study's findings also show that the system that was constructed is helpful and that it can be used as part of the digital transformation of direct payments into online payments, as well as one of the options for decreasing the spread of the pandemic. The research conducted in this journal is using quantitative research. The use of CP in Indonesia after the pandemic increased in 2019 (0.3%) and 2020 (0.6%) from the previous year. The presentation method used is secondary data and literature study. This study will compare survey results from several kinds of literature.